Reformas al régimen legal del Código de la Niñez y Adolescencia aplicable a las personas obligadas a la prestación de alimentos - Mendoza, Jaime Gustavo (2015)
The Constitution of the Republic of Ecuador contains between guarantees which protects the right to food and incorporates as it pertains to human rights and fundamental guarantees, unpublished institutional and jurisdictional arrangements to ensure the State's attention through public policies specifically designed. This has special significance for social and cultural rights, including the right to food is inscribed. The right to food is one of the most momentous enshrining the Ecuadorian legal system. It is a law aimed at protecting the very survival of children and adolescents, and ensure that the holder enjoys the necessary conditions so you can achieve your needs and that it covers the nutritious, balanced and sufficient food; comprehensive health: prevention, care and provision of medicines; education; watch out; appropriate clothing; safe, hygienic and equipped with basic services housing; transport; culture, recreation and sports; and rehabilitation and assistive if the person entitled hath any temporary or permanent disability. Importantly food right enjoyed by children and adolescents should be only the parents who are responsible people who must meet all the needs of their children. Now speaking of right to food must also speak of its subsidiary required. Today it is common to see the high level of claims against obligated called subsidiary under the new reform, lack of staff required is the parent of the child, and is more common to see huge pressure against staff requests these ones. The current Code of Childhood and Adolescence in Title V Del Right Food at the Art .... 5 (130) provides: "Forced to providing aliments.- Parents are the main holders of the maintenance obligation, even in cases of limitation, suspension or deprivation of parental rights. In case of absence, incapacity or limitation of resources or disability principals, duly verified by the person who submits the competent authority shall order that the provision of food is paid or supplemented by one or more of the subsidiary must, in view of their capacity and economic and always when they are not disabled: in order: 1. Grandparents / as; 2. brothers / sisters who have completed 21 years and are not included in the cases of paragraphs two and three of the previous Article, 3. aunts / uncles ". This provision has generated a number of problems in the subsidiary obliged called, who without any liability on the procreation of children claiming foods are pressured to pay such maintenance allowances, as noted Article unnumbered of the Reform Act to Organic code of Childhood and Adolescence, are forced subsidiary; grandfathers and grandmothers, usually elderly people who can no longer work, and generated revenues of these pensions, committing an act of abuse and abuse these people seniors, who through ignorance and lack of legal advice endorse them obligations of their children regardless of economic capacity, as the Law says uncles or aunts more distant kinship grandparents also feel affected by these provisions, since they do not have any responsibility.; Big Sisters of 21 who are disabled or are studying, are exempt from this responsibility, but those who are not in these cases are also considered obliged subsidiary and will be commination the payment of such pensions and even under pressure staff. With the amendments to the Code of Childhood and Adolescence cases have been activated mothers of children in the children's father assumes no responsibility, directly pose the trial grandparents, brothers or uncles, or that more money has . It is necessary to reform the law to exempt grandparents to fulfill obligations by the irresponsibility of their children. This Act violent certain Constitutional rights of subsidiary forced basically grandparents, because in many cases they are people who do not have the resources to fulfill these obligations, that should be borne by the parents themselves. This way of enforcing the law is a contradiction with the constitutional standards, which guarantees the rights of persons seniors or older adults, who in some cases have gone to jail. According to the current Constitution ensures that people over 65 have access to a decent, equitable and inclusive as other citizens of Ecuador life, however, these rights would be violated if the grandparents have to pay the obligations their children and even worse if they are deprived of their liberty. For these reasons should be reformed this Act, particularly as it relates to prison grandparents, who have already fulfilled their obligations to parents of minors and that the Constitution guarantees them their rights, which cannot be violated with applying a secondary law. In addition, to issue a statement of these are "must take into account criteria of proportionality to force the rest of subsidiary forced